PERAN PERGURUAN TINGGI DALAM PELAKSANAAN PEMBANGUNAN DESA MELALUI PERDES - Dika Yudanto; Hanuring Ayu (Kajian Hukum, 2019)
The role of tertiary institutions can be synchronized with the mandate of Law No. 6 of 2014 concerning Villages, Diseases, and Resources that can be provided to countries that have access to rural areas, so that every resource in rural areas can achieve strength it becomes clearer. and conceptually, places that are rural destinations can be overcome in the Village Regulation (Perdesa). This is where the role of universities in making village regulations made by the village government. assistance in making Perdes by a law lecturer from the Faculty of Law will help from the design to the enactment of the Perdes, so that village regulations made clear apply, can be implemented and the results of their utilization clearly. Higher education has a major contribution in educating the lives of rural communities, by participating in the tri dharma higher education program to realize community service programs. This community service program aims to build village growth by providing assistance and helping efforts to improve human resources in rural areas through training or outreach to the community such as increasing knowledge, training to produce valuable art and managing other resources owned in rural area. . These programs can be carried out by university structures such as lecturers and student work programs (KKN). For example the countryside in the Klaten government. Normative-empirical research methods.Keywords : rural areas, university services, human resource improvement, village regulations.